2021
DOI: 10.3389/fmolb.2021.679474
|View full text |Cite
|
Sign up to set email alerts
|

An Immune-Gene-Based Classifier Predicts Prognosis in Patients With Cervical Squamous Cell Carcinoma

Abstract: Objective: Immunity plays a vital role in the human papilloma virus (HPV) persistent infection, and closely associates with occurrence and development of cervical squamous cell carcinoma (CSCC). Herein, we performed an integrated bioinformatics analysis to establish an immune-gene signature and immune-associated nomogram for predicting prognosis of CSCC patients.Methods: The list of immunity-associated genes was retrieved from ImmPort database. The gene and clinical information of CSCC patients were obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…( Beier et al, 2000 ). Yang et al found that low expression of ICOS is one of the risk factors for the prognosis of CSCC patients ( Yang H. et al, 2021 ). In GOG-9929 study, CRT and sequential ipilimumab can increase memory T cell population.…”
Section: Discussionmentioning
confidence: 99%
“…( Beier et al, 2000 ). Yang et al found that low expression of ICOS is one of the risk factors for the prognosis of CSCC patients ( Yang H. et al, 2021 ). In GOG-9929 study, CRT and sequential ipilimumab can increase memory T cell population.…”
Section: Discussionmentioning
confidence: 99%